Cześć proszę o pomoc !
Rozwiąż równanie :

a)y+3/2- (1-y) =3,5

b) 1/5(y-3) - 2/3( y- 3/5)+ 1/3=2/5-1/3(2y-3)

c)(2y+4 )/4 =1/2y+1

d)(y-2)/3 + 1/15 - (2y-5)/3 = (8-4y)/5

e) (y-5)/2 + (2y+3)/5 +1/3 = (y+7)/15 + y/2

f) 0,83x+0,82= 0,23x+ 1,52

g) 0,6x + 2(0,1x-o,1) = 0,2 (x+1)

h) 0,7(x+2) = o,4(x+1)+ 0,3x+1

i) 0,15(2x+4) = 2(1,3+0,3x) - 0,6

j) o,1 (x+1) - 0,05(3x-10)= 0,4 - 0,35x

2

Odpowiedzi

2010-03-11T19:56:01+01:00
A)y+3/2- (1-y) =3,5
y+3/2-1+y=2,5/*2
y+3-1+y=3,5
2y=3,5-3+1
2y=1,5/2
y=0,75


b) 1/5(y-3) - 2/3( y- 3/5)+ 1/3=2/5-1/3(2y-3)
1/5y-3/5-2/3y+2/5+1/3=2/5-2/3y+1/*5
y-3-10/3y+2+1=2-10/3y+5
y-10/3y+10/3y=-2-2+3+5
y=4



c)(2y+4 )/4 =1/2y+1/*4
2y+4=2y+4
2y-2y=4-4
0=0



d)(y-2)/3 + 1/15 - (2y-5)/3 = (8-4y)/5/*15
5(y-2)+1-15(2y-5)=3(8-4y)
5y-10+1-30y+75=24-12y
5y-30y+12y=10-1-75+24
-13y=90/(-13)
y=-90/13


Nie chce mi się więcej ;p
sory xD
2010-03-11T20:33:51+01:00
A) y+3*2-1+y=3,5
y+6-1+y=3,5
y+y=3,5-6+1
2y=-1,5/2
y=-0,75

b) 1*5y-15-2*3(y-0,6)+1*3=2*5-1*6y-9
5y-15-2*3y-1,8+3=10-6y-9
5y-15-6y-1,8+3=10-6y-9
5y-6y+6y=10-9+15+1,8+3
5y=20,8/5
y=4,16

c) 8y+16=1*2y+1
8y+16=2y+1
8y-2y=1-15
6y=-14/6
y=-(ułamek) (na górze) 7 (a na dole) 3

d) 3y-6+1*15-2y+5*3=40-20y
3y-6+15-2y+15=40-20y
3y-2y+20y=40+6-15-15
21y=16/21
y= (znowu ułamek) (na górze) 16 (a na dole) 21

e) 2y-10+10y+15+1*3=15y+105+2y
2y-10+10y+15+3=15y+105+2y
2y+10y-15y-2y=105+10-15-3
-5y=97/(-5)
y=-19,4

f)0,83x-0,23x=1,52-0,82
0,5x=0,7/0,5
x=1,4

g) 0,6x+0,1x-0,1=0,2x+0,2
0,6x+0,1x-0,2x=0,2+0,1
0,5x=0,3/0,5
x=0,6

h) 0,7x+1,4=0,4x+0,4+0,3x+1
0,7-0,4x-0,3x=0,4+1=1,4
0=0

i) 0,3x+0,6=2,6+0,6x-0,6
0,3x-0,6x=2,6-0,6-0,6
-0,3x=2,6/(-0,3)
x=- (ułamek) (na górze) 2,6 (a na dole) 0,3

j) 0,1x+0,1-0,15x+0,5=0,4-0,35x
0,1x-0,15x+0,35x=0,4-0,1-0,5
0,3x=-0,2/0,3
x=- (ułamek) (na górze) 0,2 (a na dole) 0,3
1 5 1